Metal Oxalates as a CO2 Solid State Reservoir: The Carbon Capture Reaction - Linda Pastero; Vittorio Barella; Enrico Allais; Marco Pazzi; Fabrizio Sordello; Quentin Wehrung; Alessandro Pavese (Clean Technologies)
To maintain the carbon dioxide concentration below the no-return threshold for climate change, we must consider the reduction in anthropic emissions coupled to carbon capture methods applied in synergy. In our recent papers, we proposed a green and reliable method for carbon mineralization using ascorbic acid aqueous solution as the reducing agent for carbon (IV) to carbon (III), thus obtaining oxalic acid exploiting green reagents. Oxalic acid is made to mineralize as calcium (as the model cation) oxalate. Oxalates are solid-state reservoirs suitable for long-term carbon storage or carbon feedstock for manufacturing applications. The carbon mineralization reaction is a double-step process (carbon reduction and oxalate precipitation), and the carbon capture efficiency is invariably represented by a double-slope curve we formerly explained as a decrease in the reducing effectiveness of ascorbic acid during reaction. In the present paper, we demonstrated that the reaction proceeds via a “pure CO2-capture” stage in which ascorbic acid oxidizes into dehydroascorbic acid and carbon (IV) reduces to carbon (III) and a “mixed” stage in which the redox reaction competes with the degradation of ascorbic acid in producing oxalic acid. Despite the irreversibility of the reduction reaction, that was demonstrated in abiotic conditions, the analysis of costs according to the market price of the reagents endorses the application of the method.